PENGARUH CORDS TRAINING TERHADAP KECEPATAN RENANG GAYA BEBAS 50 METER ATLET RENANG KU III PUTRA KLUB TIRTA PRIMA MEDAN - Michael, Indra; Fahmi, Mhd.; Raswin; Ratno, Puji; Gultom, Syamsul; Zulaini (Fakultas Ilmu Keolahragaan Unimed, 2025)
This study aims to determine the effectiveness of cords training on improving the 50-meter freestyle swimming speed of male athletes in age group (AG) III of the Tirta Prima Swimming Club in Medan. The method used was a quasi-experimental design with a one-group pretest-posttest design. The subjects of this study were male athletes in AG III of the Tirta Prima Swimming Club in Medan, totaling individuals. The instrument used was a 50-meter freestyle swimming speed test. The intervention was administered over eight weeks in the form of cords training with gradually increasing intensity and volume. The results of the study showed a significant increase in speed following the intervention, with the average time decreasing from 40.64 seconds to 39.81 seconds. The paired sample t-test yielded a significance value of 0.001 (p < 0.05), indicating that cords training has a significant effect on improving swimming speed. Therefore, this training can be considered an effective alternative method for enhancing the performance of KU III swimmers in the 50-meter freestyle event